Towards a List of Available Names in Zoology, partim Phylum Rotifera - Segers, Hendrik; de Smet, Willem H.; Fischer, Claus; Fontaneto, Diego; Michaloudi, Evangelia; Wallace, Robert L.; Jersabek, Christian D. (Zootaxa, 2012)
Many, mostly older, names of animal species are nomenclaturally problematic, either because their orthography is unstable, orthey cannot be linked reliably to a taxonomic identity, due to the lack of recognisable descriptions and/or types. Yet, they repre-sent available (sensu International Code of Zoological Nomenclature) names and must be taken into account in zoologicalworks. This situation, with available senior, yet dubious names confounding nomenclature, is undesirable. It creates uncertain-ties at a time when molecular approaches are revolutionizing our concepts of species diversity, and fails us when the currentextinction crisis calls for efficient, accurate, and constructive approaches to document, monitor, and conserve biodiversity.The International Code of Zoological Nomenclature (The Code) provides a means to address this issue by restricting avail-ability, application and orthography of names to those included in the List of Available Names in Zoology (LAN). The Code(Art. 79) allows an international body of zoologists in consultation with the Commission to propose a candidate part of theLAN for a major taxonomic field. We explore this possibility for 3570 species-group names of Phylum Rotifera (of which 665are problematic), by presenting such a candidate Rotifera part of the LAN. The web site of the International Commission onZoological Nomenclature (http://www.iczn.org) will hold both the candidate list and a forum to facilitate consultation on thecandidate list, while the list itself also can already be freely downloaded from three other Internet sites: http://fada.biodiver-sity.be, http://rotifer.ansp.org/LAN, and www.hausdernatur.at/rotifera. We give here an overview of the general approach andprocedures applied in preparation of the candidate list, and anticipate that our effort will promote the process as well as result in a standard list of names for use in taxonomy, the Global Names Architecture and other biodiversity information initiatives.